Review of Empoasca (Matsumurasca) Anufriev (Hemiptera: Cicadellidae: Typhlocybinae: Empoascini), with description of three new species from China - Liu, Yang; Qin, Dao-Zheng; Fletcher, Murray J.; Zhang, Ya-Lin (Zootaxa, 2011)
The subgenus Matsumurasca of genus Empoasca Anufriev (Hemiptera: Cicadellidae: Typhlocybinae: Empoascini) is revised with three new species described and illustrated: E. (M.) biprocessa Qin and Liu sp. nov. (southwest China: Yunnan), E. (M.) dentalis Qin and Liu sp. nov. (central southern China: Hunan) and E. (M.) spinalis Qin and Liu sp. nov. (central southern China: Henan). E (M.) diversa Vilbaste, 1968, and E. (M.) parvifacia Dworakowska, 1994, are recorded for the first time from China. Additionally, two replacement names are proposed, E. (M.) clypealata nom. nov. for E. (M.) clypeata Qin & Zhang, 2008 (preoccupied by E. clypeata Gillette & Baker, 1895) and E. (M.) quadrialata nom. nov. for E. (M.) quadrifida Qin & Zhang, 2008 (preoccupied by E. quadrifida Southern, 1982). A key to all species of the subgenus is also provided.